2001
DOI: 10.1097/00002030-200102160-00011
|View full text |Cite
|
Sign up to set email alerts
|

Method of feeding and transmission of HIV-1 from mothers to children by 15 months of age: prospective cohort study from Durban, South Africa

Abstract: Infants exclusively breastfed for 3 months or more had no excess risk of HIV infection over 6 months than those never breastfed. These findings, if confirmed elsewhere, can influence public health policies on feeding choices available to HIV-infected mothers in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
240
0
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 352 publications
(260 citation statements)
references
References 20 publications
12
240
0
8
Order By: Relevance
“…It may also increase the risk of micronutrient deficiency as human milk has low concentrations of iron and zinc (Brown et al, 1998). Breastfeeding prolongs the period of exposure to the HIV virus in babies of HIV infected mothers (Miotti et al, 1999) and early introduction of complementary foods, including water, has been associated with increased morbidity from diarrhoeal disease (Popkin et al, 1990), linear growth faltering (Caulfied et al, 1996) and increased risk of mother to child HIV transmission (Coutsoudis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It may also increase the risk of micronutrient deficiency as human milk has low concentrations of iron and zinc (Brown et al, 1998). Breastfeeding prolongs the period of exposure to the HIV virus in babies of HIV infected mothers (Miotti et al, 1999) and early introduction of complementary foods, including water, has been associated with increased morbidity from diarrhoeal disease (Popkin et al, 1990), linear growth faltering (Caulfied et al, 1996) and increased risk of mother to child HIV transmission (Coutsoudis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence now exists illustrating the role of exclusive breast-feeding (EBF) in minimizing transmission risk of HIV while promoting child health, resulting in greater HIV-free child survival (5)(6)(7) . Recently, an African-based prospective study with feeding data on 1276 infants found a low transmission risk (4 %) following 6 months of EBF, with mortality at 3 months more than double in formula-fed babies compared with EBF infants (8) .…”
mentioning
confidence: 99%
“…All children were fed with artificial milk [8][9][10][11]. They were weighed every month on the same date (the 15 th of the month) throughout their stay.…”
Section: Methodsmentioning
confidence: 99%